2016
DOI: 10.1111/ele.12653
|View full text |Cite
|
Sign up to set email alerts
|

Climate change‐associated trends in net biomass change are age dependent in western boreal forests of Canada

Abstract: The impacts of climate change on forest net biomass change are poorly understood but critical for predicting forest's contribution to the global carbon cycle. Recent studies show climate change-associated net biomass declines in mature forest plots. The representativeness of these plots for regional forests, however, remains uncertain because we lack an assessment of whether climate change impacts differ with forest age. Using data from plots of varying ages from 17 to 210 years, monitored from 1958 to 2011 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
99
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(103 citation statements)
references
References 52 publications
4
99
0
Order By: Relevance
“…Similar to previous studies (Chen and Luo 2015;Chen et al 2016;Hogg et al 2017;Searle and Chen 2017a), above-ground biomass for each individual stem was calculated for individual trees using species' specific allometric equations developed for all major boreal tree species (Lambert et al 2005;Ung et al 2008). The biomass of individual stems were summed across each plot to obtain stand-level estimates.…”
Section: Biomass Calculationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Similar to previous studies (Chen and Luo 2015;Chen et al 2016;Hogg et al 2017;Searle and Chen 2017a), above-ground biomass for each individual stem was calculated for individual trees using species' specific allometric equations developed for all major boreal tree species (Lambert et al 2005;Ung et al 2008). The biomass of individual stems were summed across each plot to obtain stand-level estimates.…”
Section: Biomass Calculationsmentioning
confidence: 99%
“…Although positive net biomass change of the world's forests is critical to offsetting global anthropogenic CO 2 emission, recent studies have demonstrated that the rate of positive aboveground biomass change has decreased with calendar year due to high biomass loss from mortality coupled with growth insufficient to offset these losses (Brienen et al 2015;Chen and Luo 2015;Chen et al 2016). The increased tree mortality in tropical forests has been attributed to shortened tree longevity associated with greater climate variability and feedbacks of faster growth on mortality (Brienen et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, AGB is considered one of the most important biochemical crop parameters [4][5][6], and correct estimation of AGB can help improve crop monitoring and yield prediction [7]. Estimation of AGB is also important for ecological research at regional and global scales [8] and has been employed in global carbon cycle [9][10][11] and climate change [12][13][14] studies.…”
Section: Introductionmentioning
confidence: 99%